3D MIMO channel modeling and simulations - Xiongwen ZHAO; Mengyuan ZHANG; Rui ZHANG; Shu LI; Leke LIN (Dianxin kexue)
The existing MIMO channel simulation models are based on two-dimensional（2D）plane and can’t match with a three-dimensional（3D）radio propagation environment.A 3D MIMO channel simulation platform based on WINNER channel model was set up.After adding the vertical dimension in the model，the array patterns should be extended from 2D to 3D and 3D MIMO channel simulations were implemented.The simulation results of 3D MIMO channel parameters were validated by comparisons with the 3D measurements for an urban micro cell，good agreements could be observed.Simulation results show that the 3D channel correlation is bigger than 2D，however， its capacity has bigger improvement compared with 2D.